Desenvolvimento de transformador de distribuição de elevada eficiência e reduzida relação peso/potência empregando núcleo amorfo e óleo vegetal isolante - Feil, Dion Lenon Prediger (2015)
The high amount of transformers connected to the Brazilian distribution system justifies the works and studies performed in order to improve the efficiency of these equipment. Any progress represents a significant improve in the yield index of a distribution system. Therefore, this work presents the design of a distribution transformer of high efficiency and low weight/power ratio, by the use of amorphous metal core and insulating vegetable oil. For that, it is proposed a project methodology of distribution transformers, considering losses reduction, in order to maximize the performance of these electrical devices. The methodology, contemplates not only the replacement of conventional silicon steel cores of amorphous metal, but also the behavior of losses in transformers accordingly to the variation of project parameters, thus reducing losses in these equipment. This effect, besides reducing energy waste, also allows the reduction of heat generation in the active part of the transformer, leading to an increase of life-cycle of these devices. Beyond this design methodology, aiming at analyzing the cooling efficiency of distribution transformers and with that improve the efficiency of these equipment, thermal simulations of geometries of radiators for the cooling systems these equipment are performed by the application of finite elements. A temperature rise test of a distribution transformer, employing amorphous metal core and the insulating vegetable oil, projected from the project methodology proposed and of the computational fluid dynamics simulation was performed in order to confirm the results.